Efficacy of Endodontic Cryotherapy in Alleviating Post-Treatment Pain after Single-Visit RCT: A Randomized Study - Prasad Chandrakant Ingale; Simran Sethi; Sukruti Suresh Babu; Khushi Rathod; Rahul Sharma; Shanu Khan (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aims to assess whether endodontic cryotherapy can effectively lower discomfort after a single root canal visit. Material and Method: Thirty-six patients aged 18–32 years requiring single-visit root canal treatment (RCT) were divided into three groups at random, with twelve people in each: group 1 (control group), group 2 (normal saline), and group 3 (cold saline). After root canal therapy was finished, group 1 got no further treatment, group 2 got standard saline irrigation at room temperature, and group 3 got cold saline irrigation at 35.6–41°F. A visual analog scale (VAS) was used to measure pain after 6, 12, 24, and 48 hours after therapy. Result: Preliminary results indicated a marked reduction in pain in group 3 relative to groups 1 and 2 at 6, 12, and 24 hours post-treatment (P < 0.05). At 48 hours, pain levels had significantly diminished across all groups, with group 3 consistently exhibiting the lowest VAS scores. Conclusion: Endodontic cryotherapy using cold saline irrigation shows significant efficacy in reducing post-treatment pain after single-visit RCT when compared to normal saline and no additional intervention. These findings suggest that integrating cryotherapy could be a valuable adjunct in endodontic pain management.